Evaluation of the senior high school program based on the required competencies of the BS Clothing Technology Program - Coruno, Danica B.
ABSTRACT This study aimed to evaluate the identified Clothing Technology-related cognitive and psychomotor skills and competencies developed from the graduates of the Senior High School (SHS) program of the Department of Education (DepEd) K-12 and to analyze how these competencies aligned with the expectation for incoming freshmen in the BS CT program. The study can be used by the faculty of the BS Clothing Technology (CT) program of the UP College of Home Economics in the revision of the present BS CT curriculum. This can also help DepEd in determining if the SHS program is implemented properly. The research was based on quantitative and qualitative data collection among SHS curriculum guide from DepEd and the syllabi of the BS CT curriculum. Document analysis, benchmarking, and unstructured interviews were the nature of the research method used. The study utilized non-probability sampling. Interpretative document analysis and evaluation through triangulation were used in the treatment of data. After analyzing the documents gathered, it was determined that there were subjects in the DepEd SHS program that align with the cognitive and psychomotor skills and competencies expected in the UP BS CT program. However, this alignment does not necessarily mean that they are the same but suggests that these are competencies that partly satisfy the requirements of the BS CT program. The results suggested that teaching strategies, availability of facilities and knowledge of the needs of the market and society should be taken into consideration in evaluating the competencies both in the BS CT and SHS programs. The evaluation of the UP BS CT program should be assessed in relation to the DepEd K-12 program.